A survey of soil fertility in turfgrass soil of Japanese golf courses by using SOFIX technique - Tran, Quoc Thinh; Islam, Zakirul; Kubo, Motoki (Asian Journal of Agriculture and Rural Development, 2025)
Japan has numerous golf courses, covering up to 0.37% of the country’s total land area. These golf courses require intensively managed turf, and the soil environment in turfgrass fields differs significantly from that in agricultural environments. To understand the characteristics of turfgrass fields in Japan, a study was conducted that constructed and analyzed a database of 178 soil samples from golf courses across the country using the soil fertility index (SOFIX) technique. The turfgrass field database was statistically compared with agricultural field databases, including upland, paddy, and orchard fields, using the Mann-Whitney U test. The results indicated that the average bacterial biomass in turfgrass fields was 6.1 × 108 cells per gram of soil, which is comparable to that in orchard and upland fields (p > 0.01). The average values for total carbon (TC), total nitrogen (TN), total phosphorus (TP), and total potassium (TK) were 9,960 mg/kg, 540 mg/kg, 390 mg/kg, and 1,560 mg/kg, respectively, with these values distributed within narrow ranges. Although the levels of TC, TN, TP, and TK in turfgrass fields were lower than those in agricultural fields (p < 0.01), the bacterial biomass remained relatively high. These findings suggest that turfgrass fields in Japanese golf courses are likely managed with similar practices, characterized by intensive application of chemical fertilizers. The high bacterial biomass is attributed to carbon sources from clipping activities and reduced fumigation practices on golf courses. Further research on the application of organic fertilizers is recommended to promote sustainable land use and improve turfgrass management practices in golf courses across Japan.